Antagonistic effect of epigallocatechin-3-gallate on neurotoxicity induced by formaldehyde. (15th January 2019) - Huang, Jiawei; Lu, Yu; Zhang, Bin; Yang, Shaoping; Zhang, Qian; Cui, Haiyan; Lu, Xianxian; Zhao, Yun; Yang, Xu; Li, Rui
Graphical abstract: Highlights: Evaluated the protective effects on the nervous system when EGCG was administered simultaneously with formaldehyde. 3 mg/m 3 formaldehyde caused learning and memory disorders in mice. EGCG activated the Nrf2 signaling pathway to relieve formaldehyde-induced neurotoxicity. The antagonistic effect of EGCG on formaldehyde gradually became evident in the range of 20–500 mg/kg. Abstract: The toxicity of formaldehyde (FA) has always been of great concern, particularly since its use is unavoidable. On the other hand, epigallocatechin-3-gallate (EGCG), an active substance in tea polyphenols, has been shown to demonstrate physiological protective functions by in both epidemiological and zoological studies, particularly in the nervous system. The study described here, aims to explore whether EGCG can alleviate the neurotoxic effects induced by formaldehyde. After 14 days of exposure to 3 mg/m 3 formaldehyde, mice exhibited significant cognitive impairment. In the FA group, a significant increase in iNOS level compared with the control group was observed. The reduced GSH level was significantly decreased. The levels of IL-1β, TNF-α and Caspase-3 were obviously raised, while H&E and Nissl staining illustrated significant neuronal damage. After administering EGCG as a protective agent, all the above observed changes were reversed, and the protective effect of EGCG became gradually evident in the 20–500 mg/kg range. Immunohistochemistry results showed that EGCG could activate the Nrf2 signaling pathway, thus alleviating the oxidative damage caused by formaldehyde.